A Semi-Lagrangian Approach for Dilute Non-Collisional Fluid-Particle Flows. (16th March 2016) - Bernard-Champmartin, Aude; Braeunig, Jean-Philippe; Fochesato, Christophe; Goudon, Thierry
Abstract: We develop numerical methods for the simulation of laden-flows where particles interact with the carrier fluid through drag forces. Semi-Lagrangian techniques are presented to handle the Vlasov-type equation which governs the evolution of the particles. We discuss several options to treat the coupling with the hydrodynamic system describing the fluid phase, paying attention to strategies based on staggered discretizations of the fluid velocity.